Wtórne Uderzenie Proste w Oscylator Harmoniczny - Gryboś, R. (Engineering Transactions, 1961)
The object of the present analysis is the behaviour of a harmonic oscillator of which the vibration is excited by a weight falling from a certain height. As a consequence of the impact (which is not perfectly elastic) the weight rebounds, this being followed by another impact. It is shown that this secondary impact may cause in some cases an increase of the displacement of the oscillator in relation to the displacement produced by a single impact. Such an increase of the amplitude, called the «positive effect» of the secondary impact has been observed on a steel bar subjected to the action of a falling weight. The motion of the oscillator is discussed in the phase plane, relations being given enabling the determination of the type of the effect of the secondary impact, for known parameters of the system.